Visualizing pathway on 3D maps for an interactive user navigation in mobile devices - Mantoro, Teddy; Ayu, Media Anugerah; Ibrahim, Adamu Abubakar (IGI Global, 2019)
3D maps have become an essential tool for navigation aid. The aim of a navigation aid is to provide an optimal route from the current position to the destination. Unfortunately, most mobile devices' GPS signal accuracy and the display of pathways on 3D maps in the small screen of mobile devices affects the pathway architectural from generating accurate initial positions to destinations. This chapter proposed a technique for visualizing pathway on 3D maps for an interactive user navigation aid in mobile devices. This technique provides visualization of 3D maps in virtual 3D workspace environments which assists a user to navigate to a target location. The Bi-A* path-finding algorithm was used for establishing dynamic target location in Voronoi diagram/Delaunay triangulation. This approach could navigate more than two users in a 3D walk-space and at the same time showing their whereabouts on 3D projections mapped. The map shows the users' location in the scene to navigate from source to the target and the target also moves to the source to meet on the same physical location and image plane.